Robotic Rectal Resection With a Single-docking Technique Thanks to the Rotation of the R3 Arm. Issue 2 (April 2017) - Pesi, Benedetta; Annecchiarico, Mario; Amore Bonapasta, Stefano; Nerini, Alessandro; Perna, Federico; Bencini, Lapo; Di Marino, Michele; Coratti, Andrea
Abstract : Background: Robotic surgery for rectal resection presents some advantages compared with the traditional technique; however, it also presents some limitations, especially due to the multiple changes of surgical fields. We describe a new technique to perform low-anterior resection using single docking with the rotation of the third arm and our perioperative results. Materials and Methods: A total of 31 patients who underwent low-anterior rectal robotic resection with single-docking technique using robotic daVinci SI (Surgical Intuitive System) were included in the study. Results: The mean operative time was 338 minutes. The conversion rate was 3%. The mean time of refeeding was 1.4 days and the mean time of hospital stay was 6 days. Conclusions: Our technique allowed to use the robot for all surgical steps with a single docking, thereby reducing the cost of the hybrid technique and facilitating the operative team in the management of the robotic cart.